Contribution of slavonic translations to the textology of the homily “On Peter’s denial” by Leontius, presbyter of Constantinople. Pt. 1 - Michael Asmus (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2025)
This article presents results of the fi rst year of work of the project aimed at identifying the contribution of Slavonic translations in the textology of homilies of the mysterious Early Byzantine preacher Leontius, presbyter of Constantinople. In order to form a methodology, the 28th homily “On Peter’s Denial” (CPG 7900.16 [4594]; BHG 1488g), whose Greek version is found in the only MS of the 15th c. from the Paris collection (apart from of G. Savile’s copy kept at Oxford), was chosen. The Slavonic translation is contained in more than 25 MSs of the 13th — 17th cc. from collections of Athos, Russia and other Slavonic countries. The article is published in two parts. The first part describes the manuscript and publishing tradition of the homily “On Peter’s Denial” in the Greek and Slavonic languages. It shows the main characteristic features of the Slavonic text of the homily, outlines the employed Slavonic MSs, establishes their relationship (division into families and groups) drawing on variae lectiones. Using comparative lexicological analysis, the translation principles are formulated; the distortion of the text within the Slavonic tradition is also identifi ed. The second part of the article will show the contribution of Slavonic translations to the solution of textological problems of the Greek text of the homily.